The notion of hybridity in V.S. Naipaul’s novels: a reading of The Mystic Masseur, A House for Mr. Biswas & The Mimic Men - Saha, Sitesh Kumer (BRAC University, 2014)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Arts in English, 2014.